Analysis of Interests Changes in Japanese of UNNES Japanese Education Program Students - Fitriana, Wahyu suci Ulfah; Sudarma, Ketut (Universitas Negeri Semarang, 2016)
Foreign language skills in present global era becomes an important thing to be mastered. Its becomes background of the rapidly growth of foreign language learning in Indonesia, one of them is Japanese Education Program in Semarang State University (Unnes). Students who are studying Japanese in Japanese Education Program of Unnes had different sufficient knowledge of the Japanese language, either the different interest in Japanese language. Not all of the students in this study program have an interest in Japanese since the beginning of college entrance. However, after through the Japanese learning process, there are students who are experienced of interests changes in Japanese, either the increased interest or decreased interest. Based on the explanation, the research issues are what the kind of interests changes of Unnes Japanese Education Program Students, and what factors are influencing that interests changes. The purpose of this research are to know the interests changes of Unnes Japanese Education Program Students and to know the factors that influencing that interests changes. The research used descriptive quantitative approach. Research collecting data used questionnaire instrument. The questionnaire type is a mix type of open and closed questionnaire. Data were analyzed used descriptive quantitative method. The research result showed 32,5% of interests changes in Japanese of Unnes Japanese Education Program Students. The changes is 12,5% of increased interest and 20% of decreased interest. The factors that influencing the interests changes is dominated by feeling or emotions factor(87%).